MAKNA KERINDUAN DALAM LAGU "PULANGLAH UDA" KARYA SYAM TANJUNG DAN YONGKY RM: ANALISIS SEMIOTIKA FERDINAND DE SAUSSURE - rahmi elisa; Fitria Yuliani (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2026)
This study analyzes the meaning of longing (kerinduan) contained in the lyrics of the song "Pulanglah Uda" by Syam Tanjung and Yongky RM using Ferdinand de Saussure's semiotic theory. The song, written in the Minangkabau language, represents the emotional expression of Minangkabau society closely associated with the tradition of merantau (migration). This research employed a qualitative approach with textual analysis method based on Saussure's semiotics, examining the relationship between signifier and signified through syntagmatic and paradigmatic analysis. To ensure data validity, triangulation of sources, theories, and methods was applied. The results show that the meaning of longing in this song is not singular but constructed through a system of linguistic signs operating within the Minangkabau language and culture. The study found that longing in the song is articulated through five main dimensions: temporal distance and absence, emotional suffering, anticipation and hope, memory and nostalgia, and inner anxiety. The theoretical contribution of this study lies in demonstrating how Saussure's structural semiotics can be applied concretely to analyze regional song texts as a system of cultural communication. The song "Pulanglah Uda" is not merely an entertainment work, but a cultural communication system that deeply constructs the meaning of longing and reflects the identity values of Minangkabau society, particularly in the context of the merantau tradition. Keywords: Cultural Communication, Ferdinand De Saussure Semiotics, Meaning of Longing, Minangkabau Song, Song Lyrics.